The Incidence of Cancer in a Population‐Based Cohort of Canadian Heart Transplant Recipients - Jiang, Y.; Villeneuve, P. J.; Wielgosz, A.; Schaubel, D. E.; Fenton, S. S. A.; Mao, Y. (American journal of transplantation, 2010)
To assess the long‐term risk of developing cancer among heart transplant recipients compared to the Canadian general population, we carried out a retrospective cohort study of 1703 patients who received a heart transplant between 1981 and 1998, identified from the Canadian Organ Replacement Register database. Vital status and cancer incidence were determined through record linkage to the Canadian Mortality Database and Canadian Cancer Registry. Cancer incidence rates among heart transplant patients were compared to those of the general population. The observed number of incident cancers was 160 with 58.9 expected in the general population (SIR = 2.7, 95% CI = 2.3, 3.2). The highest ratios were for non‐Hodgkin's lymphoma (NHL) (SIR = 22.7, 95% CI = 17.3, 29.3), oral cancer (SIR = 4.3, 95% CI = 2.1, 8.0) and lung cancer (SIR = 2.0, 95% CI = 1.2, 3.0). Compared to the general population, SIRs for NHL were particularly elevated in the first year posttransplant during more recent calendar periods, and among younger patients. Within the heart transplant cohort, overall cancer risks increased with age, and the 15‐year cumulative incidence of all cancers was estimated to be 17%. There is an excess of incident cases of cancer among heart transplant recipients. The relative excesses are most marked for NHL, oral and lung cancer. This nation‐wide cohort follow‐up study demonstrates an excess of incident cases of cancer among 1703 heart transplant recipients in Canada, particularly lymphoma, oral cancer and lung cancer.